Sydäninfarkti ja sen vaaratekijät turkulaisilla 25-64-vuotiailla vuosina 1972-1988 - Immonen-Räihä, Pirjo (Turun yliopiston julkaisuja. Sarja C. Scripta lingua Fennica edita, 1992)
English summary: Myocardial infarction and risk factors in the City of Turku amongst citizens aged 25-64 years in the years 1972-1988.